2021
DOI: 10.1021/acscatal.1c00129
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Phosphatase-like Mimic Built from the Self-Assembly of De Novo Designed Helical Short Peptides

Abstract: Enzymes play vital roles in catalyzing biochemical reactions with high activity and selectivity, which is largely attributed to the delicately organized structure and groups at catalytic domains. Reconstruction of the enzymatic catalytic domains in artificial systems, to produce enzyme-like mimic, has become an attractive but challenging subject. Herein, inspired by the helical structure in the catalytic center of natural phosphatases, we created a phosphatase-like mimic through the self-assembly of de novo de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 72 publications
0
31
0
Order By: Relevance
“…The undeniable performance of fullerene enzyme mimics in phosphoester hydrolysis reactions, biomineralization, and osteoinduction is unique among the other artificial catalysts such that they simultaneously recapitulate the catalytic and metabolic activity of native enzymes. Furthermore, they have significantly higher catalytic efficiencies for the hydrolysis of pNPP than one of the most promising peptide‐based phosphatase mimics in literature, [ 24 ] taking advantage of the hydrophobic tuning by the nonfunctionalized fullerene parts [ 39 ] and a greater portion of active groups that synergistically interact with each other due to clustering spherical structures rather than the linear arrangement of active groups. Structural, chemical, and surface features of fullerene molecules distinguish them from the peptide‐based and organic molecule‐based artificial catalysts, which are far more stable than peptide‐based enzyme mimics and less toxic and soluble compared to organic molecule‐based enzyme mimics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The undeniable performance of fullerene enzyme mimics in phosphoester hydrolysis reactions, biomineralization, and osteoinduction is unique among the other artificial catalysts such that they simultaneously recapitulate the catalytic and metabolic activity of native enzymes. Furthermore, they have significantly higher catalytic efficiencies for the hydrolysis of pNPP than one of the most promising peptide‐based phosphatase mimics in literature, [ 24 ] taking advantage of the hydrophobic tuning by the nonfunctionalized fullerene parts [ 39 ] and a greater portion of active groups that synergistically interact with each other due to clustering spherical structures rather than the linear arrangement of active groups. Structural, chemical, and surface features of fullerene molecules distinguish them from the peptide‐based and organic molecule‐based artificial catalysts, which are far more stable than peptide‐based enzyme mimics and less toxic and soluble compared to organic molecule‐based enzyme mimics.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrolysis or deesterification reactions can be facilitated through this catalytic action, and it has also been shown that this combination can be used for the cleavage of phosphate esters. [10,24] The scaffold selection is another important contributor to catalytic action, and selfassembling scaffolds presenting multifunctional units are ideal for developing effective nanocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…94 Inspired by this, there have been very few attempts in the recent past to mimic the P-O bond breaking ability of this complex enzyme via minimal self-assembling systems. [95][96][97][98][99] Guler and co-workers have designed a diimidazole containing peptide amphiphile (Lauryl-VVAGHH-Am) that self-assembled into catalytic nanofibers to show phosphatase like activity (Fig. 4a).…”
Section: Peptide Based Self-assembly As Phosphoesterasementioning
confidence: 99%
“…Very recently, enthused by the helical catalytic domain of metal free phosphatase, He and co-workers developed heptapeptide containing self-assembled nanostructures with the ability to mimic the active site of phosphatases. 96 To design a helical configuration, the 'abcdefg' rule has been followed where hydrophobic phenylalanine was placed at a and d positions. a-Aminoisobutyric acid (Aib) was placed at c, e and g positions to overcome the thermodynamic barrier to fold in a helical manner (Fig.…”
Section: Peptide Based Self-assembly As Phosphoesterasementioning
confidence: 99%
See 1 more Smart Citation